Evaluasi Kesesuaian Lahan Sumba Tengah Untuk Tanaman Pangan Serta Perancangan Pola Tanamnya Yang Spesifik Lokasi - Banjarnahor, Dina; Simanjuntak, Bistok Hasiholan (Bumi Lestari; Vol 16 No 2 (2016), 2016)
The regency of Sumba Tengah in the province of East Nusa Tenggara relies on rainfall to support its dry land agriculture hence should be supported with land suitability evaluation and cropping pattern design for a more sustainable crop production. This study aims to evaluate land suitability for food crops in Sumba Tengah and formulate the appropriate precipitation-based cropping patterns. This work was carried out from March to June 2015. Stages of research were: 1) characterizing land attributes (climate and soil) by soil analysis and desk study, 2) assessing land suitability level by comparing land attributes and crops requirements, and 3) composing feasible cropping patterns by using water balance method. Soils of Sumba Tengah varied from sandy to clayey with low to neutral pH and low to very high content of organic carbon and nitrogen. Phosphate and potassium availability was very low. Sumba Tengah was exposed to only four wet months a year with annual precipitation of less than 2000 mm. This region was highly and moderately suitable for growing paddy, maize, tubers, and legumes. It was not suitable for wheat. Some of the northern part was arable merely for one cropping season in a year, mostly from December to April, with the alternative of growing paddy or other crops. The remaining was likely to cultivate for two cropping seasons. Legumes were recommended to include in the rotation for soil conservation. Shortage of irrigation led to the unlikeliness of three cropping seasons in a year.
Keywords: land suitability; cropping pattern; food crops; dry land; Sumba Tengah